Furanosesterterpenes from the marine sponge Ircinia echinata (Keller, 1889) - Trang, Do Thi; Dung, Duong Thi; Nhiem, Nguyen Xuan; Tai, Bui Huu; Yen, Pham Hai; Tuan Anh, Hoang Le; Thung, Do Cong; Minh, Chau Van; Kiem, Phan Van (Vietnam Journal of Chemistry, 2016)
Four furanosesterterpene, (7E,12E,20Z,18β)-variabilin (1), (12E,20Z,18β)-8-hydroxyvariabilin (2), (7E,11E,3β)-3,7,11-trimethyl-14-(furan-3-yl)tetradec-7,11-dienoic acid (3), and furoscalarol (4), and one sterol, 3β-hydroxycholest-5-en-7-one (5) were isolated from the methanol extract of the sponge Ircinia echinata (Keller, 1889). Their structures were elucidated by 1D and 2D-NMR spectra and in comparison with those reported in the literature. Keywords. Sponge, Ircinia echinata, furanosesterterpene, sterol.